Hedonic And Quality Analysis Of Chiffon Cake With Purple Sweet Potato Flour Substitution - Mahfud, Tuatul; Kusuma, Bambang Jati (JST (Jurnal Sains Terapan), 2016)
The purpose of this study is (1) to determine differences in color chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour; (2) to determine differences in flavor of chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour; (3) to determine differences in texture of chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour; (4) to determine the level of consumer preferences to color of chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour; (5) to determine the level of consumer preferences on taste of chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour; (6) to determine the level of consumer preferences on the texture of chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% of wheat flour. In this research, there are two stages of research, the first phase of preliminary studies using a type of experimental research and the second phase of research using organoleptic research approach. The population in this study is the purple sweet potato in Balikpapan and the sample used is purple sweet potato with a weight of 5 kg. Panelists were selected is a trained panel (semi-trained panel), which amounted to 25 skilled panelists. These skilled panelists are the student of Food and Beverage department in State Polytechnic of Balikpapan. Distribution of questionnaires to hedonic test and quality are done in one repetition. Data Analysis used is statistical inferential and one way ANOVE analysis using the SPSS 20.0 For Windows to see the level of preference of panelists and the hedonic quality of chiffon cake with the substitution of purple sweet potato in 50%, 75%, and 100% of the flour that includes aspects of taste, color and texture. The results showed that (1) there is a difference of color in chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% from wheat flour; (2) there is a difference of taste in chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% from wheat flour; (3) there is a differences of texture in chiffon cake which is substituted with purple sweet potato flour in 50%, 75%, and 100% from wheat flour; (4) The panelists liked the color of chiffon cake with purple sweet potato flour substitution in 100% from wheat flour; (5) panelists liked the flavor of chiffon cake with purple sweet potato flour substitution in 100% from wheat flour; (6) panelists liked the texture of chiffon cake with purple sweet potato flour substitution in 50% from wheat flour.Â Â